Eco-Friendly Conductive Hydrogels: Towards Green Wearable Electronics - José María Calderón Moreno; Mariana Chelu; Monica Popa (Gels)
The rapid advancement of wearable electronics has catalyzed the development of flexible, lightweight, and highly conductive materials. Among these, conductive hydrogels have emerged as promising candidates due to their tissue-like properties, which can minimize the mechanical mismatch between flexible devices and biological tissues and excellent electrical conductivity, stretchability and biocompatibility. However, the environmental impact of synthetic components and production processes in conventional conductive hydrogels poses significant challenges to their sustainable application. This review explores recent advances in eco-friendly conductive hydrogels used in healthcare, focusing on their design, fabrication, and applications in green wearable electronics. Emphasis is placed on the use of natural polymers, bio-based crosslinkers, and green synthesis methods to improve sustainability while maintaining high performance. We discuss the incorporation of conductive polymers and carbon-based nanomaterials into environmentally benign matrices. Additionally, the article highlights strategies for improving the biodegradability, recyclability, and energy efficiency of these materials. By addressing current limitations and future opportunities, this review aims to provide a comprehensive understanding of environmentally friendly conductive hydrogels as a basis for the next generation of sustainable wearable technologies.